You need to substitute `y cos theta` for `x sin^3 theta` in equation x `sin^3 theta + y cos^3 theta = sin theta*cos theta` such that:

`y*cos theta*sin^2 theta + y cos^3 theta = sin theta*cos theta`

You should factor out `y cos theta ` such that:

`y cos theta(sin^2...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to substitute `y cos theta` for `x sin^3 theta` in equation x `sin^3 theta + y cos^3 theta = sin theta*cos theta` such that:

`y*cos theta*sin^2 theta + y cos^3 theta = sin theta*cos theta`

You should factor out `y cos theta ` such that:

`y cos theta(sin^2 theta + cos^2 theta) = sin theta*cos theta`

You should remember that `sin^2 theta + cos^2 theta = 1` such that:

`y cos theta = sin theta*cos theta`

Reducing by `cos theta` yields:

`y = sin theta`

You should substitute `sin theta` for y in equation `x sin theta = y cos theta` such that:

`x sin theta = sin theta*cos theta`

`x = cos theta`

You should raise to square x and y such that:

`x^2 = cos^2 theta ; y^2 = sin^2 theta`

You need to add `x^2` and `y^2` such that:

`x^2 + y^2 = cos^2 theta + sin^2 theta`

**By fundamental formula of trigonometry yields `cos^2 theta + sin^2 theta = 1` , hence `x^2 + y^2 = 1` .**